(untitled) (Research, Society and Development, 2022)
This study aims to analyze the diagnosis of autism spectrum disorder (ASD) and its impacts on the family, as well as the importance of the psychologist in this process. As a research methodology, the integrative review through the literature investigation process was used, using the Scientific Electronic Library Online (SCIELO) research bases, the VHL Regional Portal platform and the Electronic Journals in Psychology (PEPSIC), between the months of July and August 2022, the descriptors (in Portuguese and English) were found on the Decs platform; Autism Spectrum Disorder; childhood autism; autism. The included studies are presented in a summary table and the analysis of the results is carried out in an expository way, each person diagnosed with autism spectrum disorder is unique, so we can see in this study that the consequences for the family are enormous, being necessary a continuous process of post-diagnosis adaptation. Consider that the family has a relevant and impacting role in the diagnosis of ASD, as the parents of the diagnosed child tend to go through many changes and difficulties during this process, seeking to understand the different symptoms that the child presents.